The Effect of Topical Application of Lavender Essential Oil on Pain Severity during Intravenous Catheterization: A Randomized Clinical Trial - Hamide jometondoki; Fereshteh Ghorat; Mohammad Hassan Rakhshani; Hasan khalili (Journal of Research Development in Nursing and Midwifery, 2019)
Background: Intravenous catheterization is one of the most common invasive interventions in the nursing profession which is associated with pain and patient dissatisfaction. The aim of the present study was to investigate the effect of topical lavender essential oil on the severity of pain caused by intravenous catheterization. Methods: This randomized clinical trial performed on 66 elective surgery candidates in Shahid Beheshti Hospital of Sabzevar in 2017. The eligible patients was recruited through convenient sampling method considering inclusion criteria they were then randomly allocated into intervention (n=33) and placebo (n=33) groups using permutation blocks. 3 puffs of lavender essential oil were used onto the insertion sites of patients in the intervention group, while in the placebo group there were applied 3 puffs of distilled water. Severity of pain was measured using Visual Analogue Scale (VAS) at immediate, 5 and 10 minutes after intravenous catheterization. Data was presented descriptive statistics and analyzed using Chi-square and Mann-Whitney in SPSS-16. The P-value less than 0.05 considered significant. Results: The mean score of pain severity in the intervention group immediately, 5 minutes and 10 minutes after the intravenous catheterization was 3.00±2.23, 1.36±1.08 and 0.51±1.14, while in patient of placebo group was 5.72±2.46, 3.12±2.23 and 1.8±1.50 respectively, there was a statistically significant difference between groups. Conclusions: The present study showed that the use of topical lavender essential oil is effective in decreasing pain severity caused by the intravenous catheter insertion. Therefore, the topical lavender essential oil can be used to prevent pain in patients before catheter insertion.